‘Errer’ en mots et en images à l’époque romantique - Patricia Viallet (Recherches Germaniques)
Along with the Sehnsucht, which is linked to it thematically, the Wanderung is one of the entry points to the Romantic universe. The writings of Ludwig Tieck or Joseph von Eichendorff, among others, are populated by tireless Wanderer figures, who can also be found (although to a lesser degree) in paintings from the same era. This analysis focuses on one specific modality of Wanderung, when it becomes random, with no guarantee of return whatsoever, and therefore becomes wandering. Among the various constitutive features of this motif in German Romantic literature, that of the gap is particularly significant, and even underpins the modern reflection on wandering. In this ‘space between’, this gap which wandering gives access to, a “poetics of the place” (A. Laumonier) is eventually outlined, which reconciles wandering with rootedness and, paradoxically, sedentarization.